Effects of Suppository Acetaminophen, Bupivacaine Wound Infiltration, and Caudal Block With Bupivacaine on Postoperative Pain in Pediatric Inguinal Herniorrhaphy - Hosseini Jahromi, Seyed Abbas (Kowsar, 2012)
BACKGROUND: The control of postoperative pain is important in children, and poor pain control leads to organ dysfunction and behavioral problems. OBJECTIVES: We compared the analgesic effects of suppository acetaminophen, bupivacaine wound infiltration, and caudal block with bupivacaine on postoperative pain in pediatric inguinal herniorrhaphy. PATIENTS AND METHODS: In this double-blinded, randomized controlled clinical trial, 90 children of American Society of Anesthesiologists (ASA) grade I-II, aged between 3 months and 7 years, and scheduled for elective unilateral inguinal herniorrhaphy under general anesthesia were assigned to three equal groups. Patients in the first group received 20 mg/kg of suppository acetaminophen. In the second group, 2 mg/kg of 0.5% bupivacaine was infiltrated in the incisional site, and in the third group, a caudal block was performed with 0.75 mL/kg of 0.25% bupivacaine. The Face, Legs, Activity, Cry, Consolability (FLACC) pain scale was applied 30 minutes after operation. Thereafter, the FLACC score was obtained every hour during the next 6 hours. If the FLACC score was 4 or over, we administered 0.5 mg/kg of intravenous meperidine. The data was transferred to SPSS-10 software and analyzed statistically with chi-square and analysis of variance tests. P < 0.05 was considered significant. RESULTS: The mean analgesic duration in the acetaminophen, bupivacaine infiltration, and caudal block groups was 4.07, 5.40, and 5.37 hours, respectively. Significant differences were not observed between the bupivacaine infiltration and caudal block groups (P = 0.9), but the differences between the bupivacaine infiltration and acetaminophen groups (P = 0.034) and the caudal block and acetaminophen groups (P = 0.039) were significant. With regard to meperidine administration, significant differences were not observed between the bupivacaine infiltration and caudal block groups (P = 0.848), but significant differences were observed between these two groups and the acetaminophen group (P < 0.05). CONCLUSIONS: Patients in the bupivacaine infiltration and caudal block groups had less postoperative pain than those in the acetaminophen group and received lower amount of meperidine. We concluded that in children, bupivacaine infiltration and caudal block with bupivacaine produce better analgesia than suppository acetaminophen. It seems that bupivacaine infiltration is better than caudal block because of its simplicity, lower incidence of complications, and failure rate.